The efficacy of continuous-flow cryo and cyclic compression therapy after hip fracture surgery on postoperative pain: design of a prospective, open-label, parallel, multicenter, randomized controlled, clinical trial - Leegwater, Nick C (BMC, 2022)
10.1186/s12891-016-1000-4